Sorting And Retrieval Robotic System Controlled Via Programmable Logic Controller For Library Usage - Ab Rashid, Mohd Zamzuri; Mohd Shah, Hairol Nizam; Jaafar, Hazriq Izzuan; Mohd Aras, Mohd Shahrieel; Sayed Nordin, Sayed Kushairi (SERC, 2014)
-